Impact of Organizational Structure on Development Strategy under Equity‐Based Incentives. Issue 4 (21st November 2020) - Li, Zhaolin; Lu, Steven Q.; Ryan, Jennifer K.; Sun, Daewon
Abstract : This study considers the product development process for a start‐up that relies on equity‐based incentives to motivate effort by vendors who are hired to contribute to the development process. We study how the organizational structure of the start‐up affects the choice between sequential and concurrent development using a two‐task model, in which both tasks must be completed for the start‐up to earn revenue. We study several organizational structures, which differ in terms of task allocation, including centralized development, joint development, and decentralized development with one or two vendors. In the joint development and decentralized structures, the vendors must determine the amount of effort to exert on each task, where the probability that the task can be completed is increasing in effort. In exchange for effort, each vendor is offered a percentage of the revenue earned by the start‐up upon completion of the project. The start‐up must determine whether the tasks should be performed concurrently or sequentially, as well as the incentive rate to offer the vendors. We find that organizational structure plays a major role in determining the optimal development strategy. In a centralized setting, where both tasks are performed in‐house, the sequential development strategy is preferred. However, in a decentralized setting, where a single vendor performs both tasks, the opposite may occur. This is due, in part, to the inefficiency caused by the vendor's forward‐looking behavior under sequential development. This same result does not occur in a decentralized setting with two vendors or in the joint development setting.